A Portable Insole Pressure Mapping System - Kian Sek Tee; Yogindra Syam Hari Javahar; Hashim Saim; Wan Nurshazwani Wan Zakaria; Safinaz Binti Mohd Khialdin; Hazlita Isa; M. I. Awad; Chin Fhong Soon (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The human locomotion is studied through gait analysis and is best observed instrumentally rather than observing visually. Thus, a portable insole pressure mapping system is built to assist in studying the human gait cycle. The pressure distribution is determined by instrumentally mapping the insole using force sensitive resistive sensors that are connected to Arduino UNO via cables. The values are saved into a secure digital card that could be post processed. Hardware and software design phase are executed for the development of this project. The outcomes match to the knowledge of human gait definitions in static posture and normal walking.